Revealing Potential Initial Mass Function Variations with Metallicity: JWST Observations of Young Open Clusters in a Low-metallicity Environment - Chikako Yasui; Natsuko Izumi; Masao Saito; Ryan M. Lau; Naoto Kobayashi; Michael E. Ressler (The Astrophysical Journal)
We present the substellar mass function of star-forming clusters (≃0.1 Myr old) in a low-metallicity environment (≃−0.7 dex). We performed deep JWST/NIRCam and MIRI imaging of two star-forming clusters in Digel Cloud 2, a star-forming region in the outer Galaxy ( R _G ≳ 15 kpc). The very high sensitivity and spatial resolution of JWST enable us to resolve cluster members clearly down to a mass detection limit of 0.02 M _⊙ , enabling the first detection of brown dwarfs in low-metallicity clusters. A total of 52 and 91 sources were extracted in mass- A _V -limited samples in the two clusters, from which initial mass functions (IMFs) were derived by model-fitting the F200W band luminosity function, resulting in IMF peak masses (hereafter M _C ) $logM_{C}/M_{\odot }\simeq -1.5± 0.5$ for both clusters. Although the uncertainties are rather large, the obtained M _C values are lower than those in any previous study ( $logM_{C}/M_{\odot }\sim -0.5$ ). Comparison with the local open clusters with similar ages to the target clusters (∼10 ^6 –10 ^7 yr) suggests a metallicity dependence of M _C , with lower M _C at lower metallicities, while the comparison with globular clusters, with similarly low metallicities but considerably older (∼10 ^10 yr), suggests that the target clusters have not yet experienced significant dynamical evolution and remain in their initial physical condition. The lower M _C is also consistent with the theoretical expectation of the lower Jeans mass owing to the higher gas density under such low metallicity. The M _C values derived from observations in such an environment would place significant constraints on the understanding of star formation.